2009
DOI: 10.1080/10409280802581268
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Ethnicity and Variation in Context: The Implications for Classroom Quality

Abstract: Abstract:Research Findings: The current study examined the differences in global quality between classrooms with African American teachers and European American teachers. The study included 1,687 classrooms (802 with African American teachers and 885 with European American teachers). Initial analyses revealed significant differences in overall global quality as well as on 2 factor scores: Language/Interactions and Activities/Materials. However, when an analysis of covariance was conducted controlling for numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Public schools have been criticized for inequitable availability of high-quality education based on race and class (Ladson-Billings, 2006), and there is evidence that the early care and education sector is following a similar path (Cassidy, Lower, Kintner, & Hestenes, 2009;Howes et al, 1995;Kontos, Howes, Shinn, & Galinsky 1997;Wrigley, 1991). As states develop and refine their TQRISs, it is important to understand relations between community contexts and the quality of early care and education available within communities.…”
Section: Community Characteristics and Associations With Qualitymentioning
confidence: 99%
“…Public schools have been criticized for inequitable availability of high-quality education based on race and class (Ladson-Billings, 2006), and there is evidence that the early care and education sector is following a similar path (Cassidy, Lower, Kintner, & Hestenes, 2009;Howes et al, 1995;Kontos, Howes, Shinn, & Galinsky 1997;Wrigley, 1991). As states develop and refine their TQRISs, it is important to understand relations between community contexts and the quality of early care and education available within communities.…”
Section: Community Characteristics and Associations With Qualitymentioning
confidence: 99%
“…This work underscores the need to examine community resources and ensure that the ECE system is supporting programs in an equitable manner such that programs do not perpetuate the gap in educational opportunity across communities. In a study comparing the quality of classrooms based on the racial or ethnic background of ECE teachers, Cassidy et al (2009) found that African American teachers had statistically lower scores on a measure of classroom quality than did European American teachers. However, when contextual variables-level of education, years of experience in early childhood, total number of teachers in the classroom, teacher-child ratio, proportion of children on subsidy, proportion of African American children in the class, and racial/ethnicity of the observer-were considered as covariates, no differences by race or ethnicity of the teacher were found, thus pointing to the role of systemic inequities in resources and opportunities that support ECE teachers and classrooms.…”
Section: Community Context Of Support For Families With Children In Cmentioning
confidence: 99%
“…Community socioeconomics are often reflected within ECE programs and are often an indicator of the family income and diversity of the children enrolled. Several studies by Cassidy and colleagues (e.g., Cassidy, Lower, Kintner, & Hestenes, ) have found socioeconomic indicators of the community to be related to the quality of ECE services received by children and their families. This work underscores the need to examine community resources and ensure that the ECE system is supporting programs in an equitable manner such that programs do not perpetuate the gap in educational opportunity across communities.…”
Section: Teachers' Role In Quality Early Learning Environmentsmentioning
confidence: 99%